Empowerment: a Necessary Attribute of a Learning Organization? - Mishra, Bijaya; Bhaskar, A. Uday (Organizations and Markets in Emerging Economies, 2010)
Purpose: The purpose of this paper is to study the role of empowerment in a learning organization. This research tries to explore whether empowerment is a necessary attribute for organizations to enhance their learning capability or not. It attempts to address two fundamental questions:• What is the role of empowerment in an organization’s learning capability?• Is empowerment an essential attribute of a learning organization?Methodology: The study adopted a mixed method of research design, which includes both qualitative and quantitative methods of data collection and analysis. The quantitative survey comprised of two questionnaires was used to survey 213 executives from various IT organizations. Interviews were also conducted with executives of two case organizations where in-depth study was conducted. Qualitative data was analyzed using the grounded theory methodology.Findings: The findings indicate that only the decision making dimension of empowerment has emerged as a significant predictor of organizational learning, not the power sharing and people valuing dimensions. Further, no difference is observed in high and low learning organizations on their empowerment pattern.Research Limitations/Implications: The sample organizations were from one geographical location (National Capital Region) of India and the study was conducted in the IT sector only. Future studies may investigate this further in different regions and sectors.
Keywords: organizational learning; empowerment; information technology; mixed method